EFEKTIVITAS FORMULASI BIOHERBISIDA EKSTRAK BUAH LERAK DENGAN PENAMBAHAN ADJUVAN TERHADAP PERKECAMBAHAN GULMA Ludwigia octovalvis - Pujisiswanto, Hidayat; Sunyoto, Sunyoto; Sriyani, Nanik; Pratiwi, Melinda Tri (JURNAL AGROTROPIKA, 2020)
The abundance of weeds in cultivated land can directly inhibit competition of plants growth. Weed control using bioherbicides is one of eco-friendly alternative. This research aims to determine the bioherbicide formulation of lerak fruit extract with the addition of adjuvants which can inhibit the germination of Ludwigia octovalvis. The research was conducted at the Weed Laboratory of the Faculty of Agriculture, University of Lampung in December 2019 - March 2020. The researcher used Complete Randomized Design (CRD) with four replications. The research treatments consisted of lerak fruit extract + KAO adjuvant, lerak fruit extract + VCO, lerak fruit extract + Tween, pure lerak fruit extract, and control (aquades). The results showed that the application of 50% (500 g / l) lerak fruit extract with the addition of VCO, KAO, and Tween adjuvants at a concentration of 2% (20 ml/l) was able to inhibit weed germination Ludwigia octovalvis by 95%-100%. The application of lerak fruit extract with the addition of a 2% concentration of VCO adjuvant was the most effective in inhibiting weed germination Ludwigia octovalvis. Keywords : adjuvants, Bioherbicide, Sapindus rarak, Ludwigia octovalvis, weed